The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1042/bj1720239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutrition on subcellular localization of rat fat-cell lipoprotein lipase

Abstract: This study supports the possibility for multiple subcellular forms of lipoprotein lipase. 1. The total activity of lipoprotein lipase per g of intact epididymal adipose tissue from fed rats is much higher than that from starved rats. 2. The isolated fat-cells of fed and of starved rats have lipoprotein lipase of almost the same activity per g of fat-pads. The isolated fat-cells of starved rats have a much higher proportion of total activity per g of the intact tissue than do those of fed rats. 3. Under the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…It is noteworthy that isolated adipocytes hydrolize a greater proportion of lipoprotein-glycerides than the fat pad pieces and the effect of the incubation period is much greater in the former preparation. These findings are compatible with others showing lower lipoprotein lipase activity in adipocytes than in fat pad pieces (Nilsson-Ehle, Garfinkel and Schotz 1976;Vanhove, Wolf, Breton and Glangeaud 1978). Unlike intact tissue activity during incubation, isolated adipocytes secrete substancial amounts of lipoprotein lipase to the medium (Nilsson-Ehle, Garfinkel and Schotz 1976;Stewart and Schotz 1974), making it more available for the substrate.…”
Section: Discussionsupporting
confidence: 92%
“…It is noteworthy that isolated adipocytes hydrolize a greater proportion of lipoprotein-glycerides than the fat pad pieces and the effect of the incubation period is much greater in the former preparation. These findings are compatible with others showing lower lipoprotein lipase activity in adipocytes than in fat pad pieces (Nilsson-Ehle, Garfinkel and Schotz 1976;Vanhove, Wolf, Breton and Glangeaud 1978). Unlike intact tissue activity during incubation, isolated adipocytes secrete substancial amounts of lipoprotein lipase to the medium (Nilsson-Ehle, Garfinkel and Schotz 1976;Stewart and Schotz 1974), making it more available for the substrate.…”
Section: Discussionsupporting
confidence: 92%
“…significant when incubations were made in the presence of heparin (Table 1). As pretreatment with collagenase for the isolation of adipocytes may be responsible for some of the results described in other experimental conditions (Vanhove et al, 1978), the study was also'performed with fat-pad pieces from the same animals as the isolated adipocytes. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of lipoprotein lipase in adipose tissue changes with the nutritional status and has been correlated with parallel alterations in the uptake of triacylglycerol fatty acids by the tissue (Bezman et al, 1962;Garfinkel et al, 1967;Austin & Nestel, 1968;Cryer et al, 1976). Although the importance of these changes in lipoprotein lipase activity measured in isolated adipocytes has been emphasized (Cryer et al, 1976) it has recently been shown that differences in the activity of the enzyme in adipocytes from fed and starved rats decreases when adipose tissue has been pre-treated with collagenase for adipocyte isolation (Vanhove et aL, 1978). This finding suggests that the enzyme inactivated by collagenase is extracellular and constitutes most of the augmented activity in fat-pads from fed animals as compared with starved ones.…”
mentioning
confidence: 99%
“…This has already been observed with acetone-dried powder of human or rat adipose tissues by several investigators (Etienne et al 1976;Garflnkel and Schotz l9'72;Davies, Oyer and Robinson 1974). It was reported by Vanhove, Wolf, Breton and Glangeaud (1978) that the first active fraction eluted from affinity chromatography was originated from the microsomal fractions, and the second one from the plasma membranes.…”
Section: Discussionmentioning
confidence: 61%